Analisis risiko kerja di Pabrik Kerupuk Dila menggunakan metode WERA dan NERPA - Olivia De Deus, Veronica; Perdana, Surya (Universitas Atma Jaya Yogyakarta, 2024)
This study aims to determine the level of ergonomic risk of production workers and ergonomic body posture with the proposal of aids using the Workplace Ergonomic Risk Assessment (WERA) and Novel Ergonomic Postural Assessment (NERPA) methods at the Dila Cracker Factory. Analysis of work posture using the WERA method shows a moderate level of risk with a score of 38 for printing and 37 for drying, meaning that this work needs to be reviewed and changed. The results of the NERPA method assessment show a high risk with a score of 7, requiring further research and immediate action. To reduce this risk, a design of work aids is proposed in the form of a table for printing with dimensions of 60 cm x 50 cm x 100 cm and a stacking trolley for drying with dimensions of 84 cm x 77 cm x 134 cm. The use of aids makes the worker's posture more ergonomic: straight back, 90° angle forearm, normal wrist for printing, and straight back, 22° angle forearm, 79° angle forearm for drying. This proposed assistive device reduced the WERA score to 27 and the NERPA score to 3 and 4, indicating a reduced risk of musculoskeletal injury.